Translation and Validation of the Clinician Administered PTSD Scale (CAPS-CA-5) for Portuguese Children and Adolescents - Barroca, Inês (2022)
Introduction: The aim of this study was to translate and validate into European Portuguese the CAPS-CA-5 (Clinician Administered PTSD Scale for Children and Adolescents), a semi-structured scale for the diagnosis of post-traumatic stress disorder in children and adolescents, according to the DSM-5 criteria.Material and Methods: This study was developed in three stages. In the first stage, the translation and back-translation of CAPS-CA-5 into European Portuguese was carried out. In the second stage, the version obtained in the previous step was subjected to a pre-test. In the third stage, the final version of CAPS-CA-5, the KIDCOPE questionnaires and the Depression, Anxiety and Stress Scale-Children were applied to 101 children who had experienced at least one potentially traumatic event. The children included in this study were between seven and 18 years old and had a follow-up period in a Child Psychiatry or Pediatrics Clinic in one of the three hospitals involved in this project of at least one month.Results: Regarding the confirmatory factor analysis, our results show that the CAPS-CA-5 is a suitable psychometric instrument to assess the diagnosis and symptoms severity of post-traumatic stress disorder according to DSM-5. Convergent validity was comparable to its original version. Although there were negative relationships with almost all of its clusters, these were not statistically significant when applied with the positive coping strategies of the KIDCOPE. The European Portuguese version of the CAPS-CA-5 showed a good internal consistency (Cronbach’s α for the total scale was 0.89).Conclusion: The European Portuguese version of CAPS-CA-5 has similar psychometric properties to its original version